Effect of different levels of energy and lysine on the laying performance of TANUVAS Namakkal Gold Japanese quail - K. Shibi Thomas; R. Amutha; M.R. Purushothaman; P. N. Richard Jagatheesan; S. Ezhil Valavan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The aim of the present research was to study the laying performance by feeding different levels of energy (2600, 2700 and 2800 Kcal/kg) and lysine (0.8, 0.9 and 1.0 %) in laying TANUVAS Namakkal gold quail with 18% crude protein in all the treatments. A total of 360 Japanese quails aged 7 weeks old were divided into nine equal groups of four replicates each consisting of 10 quails. The laying phase of twenty weeks was divided into five periods with 28 days duration. No significant effect on the age at sexual maturity and age at 50% egg production. Low energy level recorded significantly (P<0.05) earlier age for 90 per cent egg production. Low energy and lysine showed significantly (P<0.01) higher hen day and hen housed egg production, feed consumption (g/bird/day), feed efficiency/dozen eggs and feed efficiency/kg egg mass.